Assessment of colour vision among self-referred patients for glucose monitoring in ESUT teaching hospital, Parklane, Nigeria using Hardy-Rand-Rittler colour vision test - Ozioko, Nnenna M.; Eze, Gloria C. (International Journal Of Community Medicine And Public Health, 2024)
Background: Worldwide, diabetes mellitus (DM) is a common chronic metabolic disease that has a substantial impact on public health necessitating the need for screening populations at risk since it is linked to several sequelae, including diabetic retinopathy (DR). Despite evidence from studies linking colour vision impairments to diabetic eye disease, colour vision is not frequently tested for in diabetic eye screening protocols. Methods: This cross-sectional study aimed to evaluate the feasibility of using the Hardy-Rand-Rittler pseudoisochromatic color vision test for diabetic retinopathy (DR) screening due to its cost-effectiveness and ease of use. Conducted at ESUT Teaching Hospital, Parklane, standard eye examinations, including dilated fundus assessments and visual acuity tests, were conducted alongside color vision evaluations over a three-month period for a total of 57 patients on self-referred blood glucose monitoring appointments. Results: The research involved participants with fair glycemic control (average blood sugar level of 159.28 mg/dl). Those aged 48-57 had the highest likelihood of moderate color vision abnormalities while 73.7% of them demonstrated mild unclassified defects on the Hardy-rand- rattler colour vision testing. Conclusions: The Hardy-Rand-Rittler test for color vision could be valuable for screening older diabetes patients, particularly in resource-limited areas. Detecting anomalies early may indicate retinal disease, prompting further eye examinations and immediate intervention.